Produktivitas Benih Cabai Rawit Setelah Diperlakukan Dry Heat Treatment dan Penyimpanan - RAKA, I GUSTI NGURAH; NYANA, I DEWA NYOMAN; PRADNYAWATHI, NI LUH MADE (Agrotrop : Journal on Agriculture Science; Vol 3 No 1 (2013), 2015)
Productivity of Pepper Seeds Which are Treated Dry Heat Treatment and Storage Pepper plants (Capsicum frutescens L.) is one type of horticultural crops which is very high usage levels therefor, it is necessary to increase productivity dramatically. One effort to fulfil the need is preparing healthy seed with long shelf life . This study aims to determine the growth and yield of pepper plants whose seed was treated with dry heat treatment and storage. The experiment was conducted in Br . Marga Tengah, Kerta Village, Payangan District, Gianyar Regency, since May to October 2013. This study used a randomized block design (RBD) with two factors and four replications. The first factor is treated seeds by dry heat treatment at two levels i.e. given dry heat treatment at 70OC for 72 hours (D1) and without dry heat treatment (D0). The second factor is the storage of seeds with three levels, namely: non-stored seeds (T0), seed stored 2 months (T2) and the seeds stored for 4 months (T4). The results showed that there was no interaction between treatment with dry heat treatment and seed storage treatment of all variables of growth and yield of pepper plants. Dry heat treatment resulted the better growth and yield compared to non dry heat treatment. An increase in the number of fruit harvest as much as 33,43% and increased the weight of the fruit harvest per hectare as much as 33,79% on dry heat treatment compared with no dry heat treatment. Treatment of seed storage until the shelf life of 4 months did not affect the growth and yield of pepper plants.
Keywords: seed; pepper; dry heat treatment; storage